Pendekatan reformasi Jamāl al-Dīn al-Qāsimī (1283-1332 H.) terhadap sosioagama umat Islam di Syria - Ahmad Fariz Mohd Zaini; Umar Muhammad Noor; Ahmad Junid Ihsan (Penerbit UIS, 2025)
The division of Islam stemming from the weakness of the ‘Uthmāniyya dynasty had a major impact on the socioreligious situation of Muslims in Syria. This study was carried out to study the approach used by Jamāl al-Dīn al-Qāsimī to address this issue. This is a qualitative study with data obtained from authoritative documents such as books, theses, newspapers, and magazines. Jamāl al-Dīn al-Qāsimī placed a strong emphasis on the use of the Quran and Sunnah as the main sources of law. He called for ijtihad and rejected the practice of taqlīd, urging Muslims to use their intellect to static thinking. In addition, he expanded traditional education with modern knowledge. This research reveals that Jamāl al-Dīn al-Qāsimī’s approach to Syria’s socio-religious context was not merely theoretical, but deeply practical, offering a model for broader Islamic reform. Future researchers should be able to conduct further studies related to these approaches. This study reveals various techniques to address the problem of the backwardness of the Islamic community, especially in challenging times.